Greek, Demotic and Coptic papyri and ostraca in the Leiden Papyrological Institute: (P.L. Bat. 40) - Hoogendijk, F. A. J.; Stolk, Joanne Vera (Papyrologica Lugduno-Batava, 2023)
This volume contains the first edition of 66 papyri and ostraca in the collection of the Leiden Papyrological Institute. The texts are dated between the third century BCE and the eighth century CE and originate from Egypt. They include two Demotic literary papyri (one of which is written in Hieratic script), 19 Demotic ostraca, 44 Greek documentary papyri and one Coptic ostracon. All texts are published with transcription, translation, commentary and colour photographs
Keywords: Koptisch; Papyrus; Rijksuniversiteit Leiden / Papyrologisch Instituut; Demotisch; Griechisch